The neglected element of hand hygiene - significance of hand drying, efficiency of different methods and clinical implication: A review. Issue 2 (March 2019) - Gammon, John; Hunt, Julian
Hand hygiene is a fundamental strategy for controlling the spread of infection. Careful hand drying is integral to the process of hand hygiene, which aims to optimise the removal of potentially pathogenic microorganisms. Ineffective hand drying results in wet hands that are an infection risk increasing the potential for cross-infection, occupational contact dermatitis for healthcare practitioners, harm to patients and environmental contamination. Evidence indicates that there has been limited research regarding the significance of hand drying and the efficacy and clinical impact of different drying methods. The purpose of this review paper was to scope and evaluate the existing literature pertaining to hand drying; to examine the clinical consequences associated with wet hands for patients, healthcare practitioners and the clinical environment; to assess the efficacy of different drying methods; to consider the impact on patient safety; and to progress the research, debate and practice relating to hand drying. The methodological framework applied in this review was that of Arksey and O'Malley (2007). Twenty-one papers identified from 112 abstracts screened were included in the review. Analysis identified three primary themes emerging from the literature: (1) efficacy of hand drying methods; (2) drying method and microbial translocation, dispersion and environmental contamination; and (3) drying methods and environmental sustainability. This review highlights the equal importance of hand drying in the process of hand hygiene and suggests that the efficacy of hand drying is a critical factor in the prevention of the transfer of microorganisms to the environment, and from person to person following hand washing. In conclusion, this paper argues that greater attention needs to be given to hand drying in terms of practice, policy and research and its importance in clinical settings given greater focus.